A review on risk assessment of formulation development and technology transfer of COVID-19 vaccines - Hari v,; GNK Ganesh,; Vivek Reddy M,; Ahmed, Syed Suhaib (Vitae, 2022)
BACKGROUND: COVID-19 pandemic situation made the pharmaceutical companies develop the vaccine with different formulations in a short period. OBJECTIVES: The main objective of the review is to focus on different types of vaccine formulations available globally and the importance of technology transfer in vaccine development associated with potential risks. RESULTS: Research on vaccine development led to various types of vaccines, such as Inactivated vaccines, live attenuated vaccines, Ribonucleic acid (RNA) and Deoxyribonucleic acid (DNA) vaccines, viral vector vaccines, and Protein Subunit Vaccines for COVID-19. But the process of vaccine development and technology transfer is lined with various risks and challenges. Through risk assessment, we found some major potential risks involved in product development; this leads to a smoother and more efficient method to develop safe vaccines available for public health. CONCLUSIONS: This review will explain the significance of technology collaboration for the faster development of various formulations of vaccines globally.